Non-monotonic reasoning with normative conflicts in multi-agent deontic logic - Beirlaen, Mathieu; Straßer, Christian (Journal of Logic and Computation, 2013)
We present two multi-agent deontic logics that consistently accommodate various types of normative conflicts. Its language features modal operators for obligation and permission, and for the realization of individual and collective actions. The logic is non-classical since it makes use of a paraconsistent and paracomplete negation connective. Moreover, it is non-monotonic due to its definition within the adaptive logics framework for defeasible reasoning. The logic is equipped with a defeasible proof theory and semantics.